WORK OF SUFISM AND MORALITY’S TURKISH DESCRIPTION OF THE IDEA : GARİB-NÂME - Nadir İLHAN (Fırat University, 2021)
Great Seljuk and Anatolian Seljuk given great importance in the fields of Arabic and Persian are known . Although the reign of the owners of the public and especially Turkey and around the palace in the writing of scientific and literary works of these languages ​​other than Turkish is preferred , Turkish writers scorn is expressed in the works . Turkish by some poets and writers also use this language for their inferiority complex in this language work writing because of disability declare a period Asik Pasha as Turkish lover emerged in turkish science can be made of knowledge , wisdom of the language described can be - can be understood ; Turkish, Farsi is a language rich enough to work with Turkish beyitlik has written to 10.592 have cried . Asik Pasha , Kaplan pointed out the importance , as was established by the Ottoman Turks of the world state that the person who prepared the ideological and metaphysical foundations in our literature and mysticism were among the first representatives of the area . Kemal Yavuz 's words " ... a work of reaching the mystical secrets of Rights to give direction is also important . If the world is considered a place of homesickness Garib- nâme meaning of the name are also confronted with another . " Mystical subjects dealt with the words of the work is shown. Asik Pasha fell in love with the works of the transfer in Garib- nâme and Sufi poet influenced by similarities besides the mystical self on many later poets have been effective in terms of thought . He Turkish works of the period, the firm used in a way , has been told by many religious mystical Turkish term